Modern Constructions of China’s Exceptionalism in International Relations - Katarína Sárvári (Köz-gazdaság, 2020)
This research attempts to identify manifestations self-perception of exceptionalism in China’s long history and explain why and how different types of exceptionalism have arisen in modern periods. Analyses are historical as well as theoretical. It explores how international structure has interacted with perceptions of history and culture to produce three distinctive, yet related, types of exceptionalism in contemporary China. While not determinative, constructs of exceptionalism can suggest policy dispositions, and by being an essential part of China’s worldview, they can become an important source for policy ideas and offer the aspects for the ostensible construction of Chinese theories of international relations.